2016
DOI: 10.1080/10410236.2016.1204583
|View full text |Cite
|
Sign up to set email alerts
|

Narratives of Stress in Health Meanings of African Americans in Lake County, Indiana

Abstract: Across the life course, African Americans bear an unequal burden of disease compared to other racial groups. In spite of the widespread acknowledgment of racial health disparities, the voices of African Americans, their articulations of health and their local etiologies of health disparities are limited. In this article, we highlight the important role of communication scholarship to understand the everyday enactment of health disparities. Drawing upon the culture-centered approach (CCA) to co-construct narrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Further, over half of the African Americans in the current study reported getting “very high” from blunts (52.8%) and smoking blunts to relieve stress (59.2%). African Americans often experience a disproportionate level of stressors relative to other racial/ethnic groups (Dutta, Sastry, Dillard et al, 2016), such as racial discrimination (English, Lambert, Evans et al, 2014) and financial stress (Estrada-Martinez, Caldwell, Bauermeister, et al, 2012). It is plausible that the subjective high experienced from smoking blunts provides a temporary escape from the disproportionate levels of stress that are experienced among African Americans.…”
Section: Discussionmentioning
confidence: 99%
“…Further, over half of the African Americans in the current study reported getting “very high” from blunts (52.8%) and smoking blunts to relieve stress (59.2%). African Americans often experience a disproportionate level of stressors relative to other racial/ethnic groups (Dutta, Sastry, Dillard et al, 2016), such as racial discrimination (English, Lambert, Evans et al, 2014) and financial stress (Estrada-Martinez, Caldwell, Bauermeister, et al, 2012). It is plausible that the subjective high experienced from smoking blunts provides a temporary escape from the disproportionate levels of stress that are experienced among African Americans.…”
Section: Discussionmentioning
confidence: 99%
“…Conceptual co-optation of CBPR can often be used through cultural approaches to health campaigns such as cultural competence (CS), demonstrating healthcare professional adeptness at handling multicultural clientele and cultural sensitivity (CS), which offers communication solutions that fit the cultural agenda and health issues considered important by the health communicator (Dutta 2008, Dutta et al 2017. These oversights need to be interrogated for the tensions which they create between CBPR in theory versus CBPR in practice.…”
Section: Tensions In Cbpr Practicementioning
confidence: 99%
“…These oversights need to be interrogated for the tensions which they create between CBPR in theory versus CBPR in practice. The most prominent tensions that arise include the insider-outsider tension, inherent power differentials between partners, and the corrosion of trust in these interactions (Dillard et al 2014, Dutta et al 2017, Dutta et al 2013. As these concepts can have a direct and significant effect on the outcomes of CBPR campaign and longevity of trust development, it is pertinent that they are deconstructed in their everyday praxis.…”
Section: Tensions In Cbpr Practicementioning
confidence: 99%
See 2 more Smart Citations